Flood Rescue System Using IoT and Android Applications - Issac, Jithin Jacob; Mathew, Nidina Raichel; Ravi, Ranjitha; Regi, Reshma; MP, Imthiyas (International Journal of Computer Sciences and Engineering, 2020)
Flood Rescue System will monitor the disastrous situation and share real time details with the rescuer. This is an offline communication system, by which a user can send a message in the absence of the internet and cellular data. We have developed an IoT based android application to rescue people affected in emergency situations like flood, disaster etc. The features like live location, photo sharing and information to the rescuer can be taken. The rescuers will get the details from the database of the person who needs to be rescued in the nearby area where the rescuers belong to. The rescue operation can be done in priority wise, and it will be constituted by villagers, fishermen, army etc. These rescuers will be guided to a place that is appropriate for them. This will definitely be a huge contribution to the community, for disaster management.